Assets Inventory Information System Using Fifo Method in PT Brightfoods International's Web-Based Formulation - Muhammad Aditya Septian Sugraha; Fitria Rachmawati; Nurul Kamilah (Ilmu Komputer, FMIPA, Universitas Pakuan, 2022)
AbstractAs time goes by, the world of technology is getting more sophisticated. We can easily get all the information we want to get. Internet access is getting faster and the world of software is progressing very rapidly. This progress must be based on a balanced advance in science and technology. One of them is PT Brightfoods International, a food manufacturing company located in the Sentul Industrial Area, Bogor, which produces food to be enjoyed throughout Indonesia. Currently, the storage of goods delivery data only uses general ledgers, raw material data forms and Microsoft Excel. So there are still frequent loss of stock of goods and not according to the order of the expiration date. This research designs and builds a web-based (offline) inventory system by applying the FIFO method. This record supports the company's business process activities and helps the data storage and processing process with FIFO calculations to avoid expired materials. The web-based inventory information system application using the FIFO method produces information to make a decision desired by the user. Therefore, an application is made that can assist the owner and his employees in processing data, as well as the number of items available. The information system used is based on web and using Sublime Text Tools and Database management Using the MySQL System.Keywords:Information Systems;FIFO;Inventory;WEB;Database Abstract As time goes by, the world of technology is getting more sophisticated. We can easily get all the information we want to get. Internet access is getting faster and the world of software is progressing very rapidly. This progress must be based on a balanced advance in science and technology. One of them is PT Brightfoods International, a food manufacturing company located in the Sentul Industrial Area, Bogor, which produces food to be enjoyed throughout Indonesia. Currently, the storage of goods delivery data only uses general ledgers, raw material data forms and Microsoft Excel. So there are still frequent loss of stock of goods and not according to the order of the expiration date. This research designs and builds a web-based (offline) inventory system by applying the FIFO method. This record supports the company's business process activities and helps the data storage and processing process with FIFO calculations to avoid expired materials. The web-based inventory information system application using the FIFO method produces information to make a decision desired by the user. Therefore, an application is made that can assist the owner and his employees in processing data, as well as the number of items available. The information system used is based on web and using Sublime Text Tools and Database management Using the MySQL System. Keywords: Information Systems; FIFO; Inventory;WEB; Database